Serologic and molecular characteristics of hepatitis B virus infection in vaccinated schizophrenia patients in China - Yiying Wang; Lugang Yu; Hui Zhou; Zhiwei Zhou; Huijuan Zhu; Yinghui Li; Zhi Zheng; Xinxin Li; Chen Dong (Journal of Infection in Developing Countries)
Introduction: Previous studies have indicated that the patients with psychiatric illness were at higher risk of hepatitis B virus (HBV) infection. However, the efficacy of hepatitis B vaccine in schizophrenia patients remains unclear. Methodology: Between June 2014 and January 2015, 415 schizophrenia patients and 3,038 controls who had been routinely immunized as infants were recruited in the present study. Hepatitis B surface antigen (HBsAg), HBsAb, and HBV DNA were detected with commercial methods according to the manufacturer’s protocol. A 600-bp region of the S gene (region nt236–nt835) was amplified by nested polymerase chain reaction (PCR). The genotypes of isolated HBV were identified using phylogenetic analysis by the neighbor-joining algorithm in the software MEGA version 4.1. Results: The seroprevalence of HBsAg in schizophrenia patients was 6.75%, which was significantly higher than 3.32% measured in controls. HBsAg prevalence was 7.94% in male schizophrenia patients and 5.47% in female schizophrenia patients, while it was only 4.04% in males and 2.08% in females in the control group. The HBsAb seroprevalence rate was 58.31% in schizophrenia patients and 59.94% in non-schizophrenia controls. Moreover, one HBV strain in the schizophrenia group presented I126S vaccine escape mutation (5.88%), while three HBV isolates showed Q129H, M133L, and G145R vaccine escape mutations in the control group (6.81%). Conclusions: Schizophrenia patients are at higher risk for HBV infection, even those who had received routine immunization. Therefore, a booster HB vaccination targeted at schizophrenia patients should be considered in the future.